Development of a Mobile-Based Student Grade Processing Application Using the Waterfall Method - Muhamad Alda (ULTIMATICS, 2023)
One of the public elementary schools in Medan is SDN 064017. At SDN 064017, the procedure for processing student grade data is not yet computerized. Gradebooks are used to track and process student grade information. There are still certain problems that arise with this method. SDN 064017 requires a lot of time and effort to process and find information on student grades. The purpose of the author's research is to develop a mobile-based application that will simplify and speed up SDN 064017 in processing and searching for student grade data. The system development method used by the author is the waterfall method, consisting of requirements analysis, system design, implementation, testing, deployment, and maintenance stages, while the system testing method uses the black box testing method. In the process of developing a mobile-based application, the author uses the Kodular framework and the Airtable database. With the information system, it is hoped that it can help SDN 064017 in processing and searching student grade data at SDN 064017 to be more effective and efficient through an Android mobile.